Osprey (Pandion haliaetus) reintroduction project in Cádiz: 2003 report - Ferrer, Miguel; Casado, Eva (Fundación Migres - Migración en el Estrecho de Gibraltar, 2004)
15 pages, 6 figures, 3 tables, 4 maps.-- The Pandion haliaetus reintroduction project was developed at the Doñana Biologica Station/Estación Biológica de Doñana (EBD-CSIC). Along the preliminary stage of Osprey (Pandion haliaetus) reintroduction project in Cádiz the following activities were carried out: 1. Choosing of release area and within it, accurate point for hacking tower installation.- 2. Establishment of agreements between Andalusian Regional Environment Center and donor countries in order to guarantee the stable supply of nestlings.- 3. Building of hacking tower and other facilities. The preliminary stage of Osprey (Pandion haliaetus) reintroduction project in Cadiz (Andalusia) started in 2002, financially supported by Consejería de Medio Ambiente de la Junta de Andalucía (Andalusian Regional Environment Center). Peer reviewed